Physiological and genomic features of a novel violacein-producing bacterium isolated from surface seawater - Wu, Yue-Hong; Cheng, Hong; Xu, Lin; Jin, Xiong-Bin; Wang, Chun-Sheng; Xu, Xue-Wei (PLOS ONE, 2017)
Strains JW1T and JW3, isolated from surface seawater of the Arabian Sea, were subjected to polyphasic taxonomic analysis. Cells of both strains were Gram-stain-negative, aerobic, and rod-shaped. They formed violet pigment and produced violacein. On the basis of 16S rRNA gene sequence analysis, strains JW1T and JW3 showed high 16S rRNA gene sequence similarity with Pseudoalteromonas byunsanensis JCM12483T (98.2%), P. shioyasakiensis SE3T (97.8%), P. arabiensis JCM 17292T (97.3%), and P. gelatinilytica NH153T (97.1%). The 16S rRNA gene sequence similarity between JW1T and JW3 was 100%. Phylogenetic analyses revealed that both strains fell within the cluster of the genus Pseudoalteromonas and represented an independent lineage. The average nucleotide identity and in silico DNA-DNA hybridization values between JW1T and type strains of the closely related Pseudoalteromonas species were 70.9-83.3% and 20.0-26.4%, respectively. The sole respiratory quinone in both strains is ubiquinone 8 (Q-8). The principal fatty acids are summed feature 3 (C16:1ω7c and/or iso-C15:0 2OH), C18:1ω7c, and C16:0. The major polar lipids are phosphatidylethanolamine, phosphatidylglycerol, one unidentified glycolipid, one unidentified aminolipid, and one unidentified phospholipid. The DNA G+C content was 43.3 mol%. Differential phylogenetic distinctiveness, chemotaxonomic differences, and phenotypic properties indicated that strains JW1T and JW3 could be differentiated from the Pseudoalteromonas species with validly published names. Therefore, it is proposed that strains JW1T and JW3 represent a novel species of the genus Pseudoalteromonas, for which the name Pseudoalteromonas amylolytica sp. nov. (type strain, JW1T = CGMCC 1.15681T = KCTC 52406T = MCCC 1K02162T) is proposed.